2014
DOI: 10.1016/j.actpsy.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Recollecting positive and negative autobiographical memories disrupts working memory

Abstract: Working memory and emotion 2 AbstractThe present article reports two experiments examining the impact of recollecting emotionally valenced autobiographical memories on subsequent working memory (WM) task performance. Experiment 1 found that negatively valenced recollection significantly disrupted performance on a supra-span spatial WM task. Experiment 2 replicated and extended these findings to a verbal WM task (digit recall), and found that both negative and positive autobiographical recollections had a detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 64 publications
2
22
2
Order By: Relevance
“…As displayed in Table 2, a range of studies investigated WM storage and span capacity in healthy subjects using a variety of induction methods before the WM task ( Allen, Schaefer, & Falcon, 2014 ; Chepenik et al, 2007 ; Esmaeili, Karimi, Tabatabaie, Moradi, & Farahini, 2011 ; Mayshak, Sharman, & Zinkiewicz, 2016 ; Palmiero, Nori, Rogolino, D'Amico, & Piccardi, 2015 , 2016 ; Palmiero & Piccardi, 2017 ; Spachtholz, Kuhbandner, & Pekrun, 2014 ; Xie & Zhang, 2016 ). Only two studies included emotional pictures as the target of the WM task.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As displayed in Table 2, a range of studies investigated WM storage and span capacity in healthy subjects using a variety of induction methods before the WM task ( Allen, Schaefer, & Falcon, 2014 ; Chepenik et al, 2007 ; Esmaeili, Karimi, Tabatabaie, Moradi, & Farahini, 2011 ; Mayshak, Sharman, & Zinkiewicz, 2016 ; Palmiero, Nori, Rogolino, D'Amico, & Piccardi, 2015 , 2016 ; Palmiero & Piccardi, 2017 ; Spachtholz, Kuhbandner, & Pekrun, 2014 ; Xie & Zhang, 2016 ). Only two studies included emotional pictures as the target of the WM task.…”
Section: Resultsmentioning
confidence: 99%
“…In general, effectively induced negative mood, regardless of the method used, seems to decrease WM performance. For example, Allen et al ( 2014 ) indicated in their experiments that recollecting negative or positive autobiographical emotional memories could impair WM performance across both verbal and visual modalities assessed by the digit recall span and the Corsi span task. Similarly, Spachtholz et al ( 2014 ) showed that negative mood induction through the recollection of negative autobiographical memories and listening to music decreased the storage capacity of items but increased the quality of visuospatial WM representations compared to a neutral mood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, subjects recruit additional neural resources when performing the Sternberg WM task under cold pressor stress compared to during periods of nonstress, suggesting that stress reduces WM processing efficiency (Porcelli et al, ). Finally, both verbal and spatial WM capacity is reduced following recall of negative autobiographical memories (Allen, Schaefer, & Falcon, ), suggesting that negative mood induction has a similar detrimental effect.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that working memory is impaired in depressed individuals [24,25]. In addition, research has demonstrated that negative affect is associated with poorer working memory performance [26,27]. The Resource Allocation Model is thought to explain this observation.…”
Section: Introductionmentioning
confidence: 99%